Safety profile of anifrolumab in patients with active SLE: an integrated analysis of phase II and III trials - Tummala, Raj; Abreu, Gabriel; Pineda, Lilia; Michaels, M Alex; Kalyani, Rubana N; Furie, Richard A; Morand, Eric F (Lupus science & medicine, 2021)
ObjectiveIn phase II and III trials, anifrolumab, a human monoclonal antibody that binds type I interferon receptor subunit 1, has shown efficacy in adults with moderate to severe SLE. We evaluated the safety and tolerability of anifrolumab using data pooled from these trials to more precisely estimate the rate and severity of adverse events (AEs).MethodsData were pooled from patients receiving monthly intravenous anifrolumab 300 mg or placebo in MUSE, TULIP-1 and TULIP-2. Key safety endpoints included percentages and exposure-adjusted incidence rates (EAIRs) of patients who experienced AEs, serious AEs (SAEs), AEs leading to discontinuation and AEs of special interest.ResultsDuring treatment, 86.9% of patients receiving anifrolumab 300 mg (n=459) experienced AEs (≥1) versus 79.4% receiving placebo (n=466), and 4.1% versus 5.2% experienced an AE leading to discontinuation of investigational product. SAEs (≥1) were experienced by 11.8% and 16.7% of patients receiving anifrolumab and placebo, respectively (EAIR risk difference (95% CI) −7.2 (−12.5 to –1.9)), including lupus exacerbations classified as SAEs (1.5% and 3%, respectively). Infections occurred in 69.7% and 55.4% of patients receiving anifrolumab and placebo, respectively; difference in reported rates was driven by herpes zoster (HZ) and mild and moderate respiratory (excluding pneumonia) infections. The risk of HZ was increased with anifrolumab versus placebo (6.1% vs 1.3%, respectively; EAIR risk difference (95% CI) 5.4 (2.8 to 8.4)); most HZ events were mild or moderate, cutaneous and resolved without treatment discontinuation. Serious infections occurred in 4.8% and 5.6% of patients receiving anifrolumab and placebo, respectively.ConclusionsIn this pooled analysis of 925 patients with moderate to severe SLE, monthly intravenous anifrolumab 300 mg was generally well tolerated over 52 weeks with an acceptable safety profile. Anifrolumab was associated with an increased incidence of HZ and respiratory tract infections and lower reported rate of SLE worsening as SAEs.